The Making of a President Using Data Analytics and Social Media - Lindoo, Ed (Journal of Marketing Development and Competitiveness, 2020)
Today, political campaigns rely heavily on analytics to target potential voters. The algorithms used, as well as bias that may be introduced in the process, may skew the results and cost an election, as seen in the Clinton campaign. Additionally, Social Media plays a huge role in political races, as does fake news. More alarming is the new trend for Social Media sites to censor anyone or anything which can also make or break a campaign. In this paper we research events that affected the 2016 Presidential election and present issues that may have an effect on future elections.